AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE SONG LYRIC “BRAHMAN BABU YAU” - Dr. Vijay Kumar (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2014)
Knowing the meaning of all the words is very important to us. Language is a communication tool. In language people can get to know each other because they can understand what others around us are saying, so that you never miss a misunderstanding. But people should know what style of language the author or people use. After identification, the thesis researcher found that the biggest problem in this concept was the lack of understanding of most people in figurative language. In fact, there are still many people who do not yet understand the figurative language, not just students in general, but also teachers. For this reason, researchers are incorporating this concept. The purpose of this study was to find out the historical history of maithili language hymns, to find out the type of figurative language used in “Brahman Babu songs, and to find the most common language used in Epiphany songs. In this article, the researcher explains some of the concepts, meanings of figurative language, types of figurative language, song meaning, and meaning of words. This concept is expected to increase students’ understanding of figurative language. Through this article, people can find various types of figurative language, definitions, and examples of figurative language. Keywords: Figurative Language, Maithili Language, Bhojpuri, Metaphor, Simile